Using commonly-available technologies to create online multimedia lessons through the application of the Cognitive Theory of Multimedia Learning - Cavanagh, Thomas M.; Kiersch, Christa (Educational technology research and development, 2023)
Principles derived from the Cognitive Theory of Multimedia Learning (CTML; Mayer in: Multimedia learning, Cambridge University Press, Cambridge, 2021) provide valuable guidance for enlisting commonly-available technologies to create effective online multimedia lessons. Specifically, CTML can guide instructional designers on the use of slide-sharing programs to create concise, narrated animation segments; the use of survey programs to interpolate questions and prompts between these segments to facilitate generative learning activities; and the use of video-sharing sites to provide learners with control over relatively superficial aspects of instruction. The application of CTML to the design of online multimedia lessons raises a number of theoretical and practical questions, including the need to better understand the relationship between working memory capacity and working memory duration, the importance of retrieval as a learning process, and the relative impact of selection and organization processes on learning.